STRUCTURAL CHARACTERIZATION AND MOLECULAR DYNAMICS OF PROTEIN KINASE C EPSILON IMPLICATED IN BIPOLAR DISORDER. - S. SHANTHIPRIYA; VA DOSS (International Journal of Pharma and Bio Sciences, 2013)
Bipolar disorder (BPD) is a condition in which people go back and forth between periods of a very good or irritable mood and depression. Recently accumulated evidence indicates that an alteration in PKC activity plays a significant role in pathophysiology of BPD. Protein kinase C (PKC) is a group of calcium and phospholipid-dependent enzymes, which plays a pivotal role in cell signaling systems. Inhibition of PKC plays an important role in neuroprotection against BPD. Hence to design and study the inhibitors for BPD we modeled 3D structure of PKC using Accelrys Discovery studio software package and five models were generated. The model with best PDF total energy (-9291.1621) and best Dope score (-47210.160156) was selected and analyzed for its validation using Ramachandran plot and for prediction of active site for ligand building. This model is submitted to PMDB and can be downloaded for docking studies using accession number PM0078502 to design potent inhibitors of PKC.